(untitled) (Bangladesh Journal of Medical Science, 2013)
Objective: To evaluate the oxidative stress and antioxidant activity in pre and post hemodialysis in chronic renal failure patients using a diacetate cellulose membrane. Background: Chronic Renal Failure is a gradual, progressive and irreversible loss of normal functioning of kidneys. This is associated with increased formation of reactive oxygen species and increased oxidative stress. No studies have been undertaken in this area in Nepal. Method: The study groups were devided into chronic renal failure patients undergoing hemodialysis (n=52) and healthy controls (n=52). Diacetate cellulose was used as dialyzer membrane for chronic renal failure patients. Blood samples were collected in EDTAbottles and plasma was used for the estimation of oxidative stress marker, total antioxidant activity, vitamin C, ?-tocopherol, urea and creatinine. Results: There was significant reduction in the levels of vitamin C,? -tocopherol and total antioxidant activity in post dialysis patients compared to predialysis and control groups (p<0.001). Plasma urea and creatinine levels were high in predialysis patients compared to controls and was significantly reduced after dialysis. Significantly elevated malondialdehyde levels were found in chronic renal failure patients before and after dialysis when compared with controls. Conclusion: The results of our study indicate that there are reduced levels antioxidants in chronic renal patients in pre and post dialysis condition and also more loss of antioxidants after dialysis. All these condition leads to increased oxidative stress in these patients. DOI: http://dx.doi.org/10.3329/bjms.v13i1.14741 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 40-44